Hubungan antara Harga Diri dan Persepsi Pola Asuh dengan Ketakutan akan Intimasi pada Dewasa Awal yang Memiliki Orang Tua Bercerai - Nabila Aliya Fatah; Nurul Hartini (INSAN Jurnal Psikologi dan Kesehatan Mental, 2022)
Parental divorce will influence how a child develops their self-esteem. After divorce, the relationship between parents and their children also tends to get disturbed and become inconsistent. With regard to the developmental task during early adulthood to build intimacy with others, the aim of this study was to determine the relationship between self-esteem, perceived parenting style, and fear of intimacy. This quantitative study conducted a survey. The results revealed that self-esteem and perceived democratic parenting style were correlated with fear of intimacy among early adults with divorced parents. These correlations, however, were only weak to moderate, suggesting that future studies on fear of intimacy should consider the role of other factors.